Pengaruh Etika Kerja Islam dan Kecerdasan Emosional Terhadap Kinerja Karyawan dengan Komitmen Organisasi Sebagai Variable Mediasi dalam Perspektif Bisnis Islam di Rumah Sakit H. Kamino Baradatu Kebupaten Way Kanan Lampung - Amelia Agus Santi; Madnasir Madnasir; Siska Yuli Anita (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
This study aims to analyze the influence of Islamic work ethics and emotional intelligence on employee performance, with organizational commitment as a mediating variable among employees of H. Kamino Baradatu Hospital, Way Kanan Regency. The research employed a quantitative method with a sample of 62 respondents selected through purposive sampling, and data were analyzed using SmartPLS. The results indicate that Islamic work ethics and emotional intelligence have a positive and significant effect on employee performance, while organizational commitment does not significantly mediate this relationship. Based on these findings, it is recommended that the hospital continue to strengthen the implementation of Islamic work ethics and enhance employees’ emotional intelligence to improve performance and overall organizational productivity.